(untitled) - Honan, James P. (San francisco, 2002)
Casebook I: Faculty Employment Policies presents six cases that were developed by the Project on Faculty Appointments at the Harvard Graduate School of Education and designed to be used in a variety of instructional settings in order to explore and analyze efforts to bring about institutional change. Each case study highlights a particular challenge regarding faculty employment and illustrates these challenges using situations from actual institutions of higher education. The cases provide a wealth of background information and are filled with real-life details. In addition, the cases are comprehensive in scope and reflect the complexity of administrative decision making as experienced by academic leaders.
Keywords: College teachers,College teaching; Tenure,Evaluation; United states,United states